(untitled) (Annals of Medical Research, 2023)
Aim: In this study, it was aimed to examine the effects of metabolic syndrome, which affects many organs, on the autonomic nervous system and to observe the changes after treatment. Materials and Methods: Heart rate variability values ​​of 101 metabolic syndrome patients who were treated at the Kocaeli University Cardiology Outpatient Clinic included in the study. All patients were offered lifestyle change suggestions in addition to their medical treatments. At the end of three months, the heart rate variability parameters of the patients were re-evaluated. Results: Heart rate variability values were found to be significantly lower in metabolic syndrome patients compared to the control group. It was observed that the heart rate variability values ​​improved significantly in half of the patients who applied the given treatment with lifestyle changes. A decrease in heart rate change parameters was found in the group that did not implement lifestyle changes compared to the beginning of the study. Conclusions: Autonomic nervous system functions evaluated by heart rate variability decreased in patients with metabolic syndrome, and the treatment and lifestyle changes had a positive effect on these parameters.